2006
DOI: 10.1029/2006jc003611
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the role of wind forcing and freshwater buoyancy input on the circulation in a shallow embayment (Gulf of Trieste, Northern Adriatic Sea)

Abstract: [1] This paper investigates the role of wind forcing and river discharge on a small-scale shallow embayment: the Gulf of Trieste. The qualitative and quantitative analysis of these dominant processes is carried out using a high resolution numerical model, initialized and forced with experimental data. The simulations are focused on short-term transient events, which occurred during the stratification season (spring and summer). Two significant case studies are analyzed in detail: a strong wind event during sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…This event is represented by a significant peak in the third EOF mode amplitude (Figure 9c). In situ observations in the water column [Querin et al, 2006] revealed that the strong winds cooled the GoT and mixed the water all the way down to the bottom, breaking temporarily the stratification. The latter was not reestablished before 1 July, that is, 5 days later.…”
Section: Smentioning
confidence: 99%
See 1 more Smart Citation
“…This event is represented by a significant peak in the third EOF mode amplitude (Figure 9c). In situ observations in the water column [Querin et al, 2006] revealed that the strong winds cooled the GoT and mixed the water all the way down to the bottom, breaking temporarily the stratification. The latter was not reestablished before 1 July, that is, 5 days later.…”
Section: Smentioning
confidence: 99%
“…However, this circulation can be reversed under Bora winds. In summer 2002, a specific event of Bora during stratified conditions was studied numerically by Querin et al [2006]. In this study, satellite and in situ measurements along with numerical experiments show that strong wind events mix the water and homogenize the entire water column in a few hours.…”
mentioning
confidence: 97%
“…The Gulf experiences annual fluctuations of temperature varying from 5°C to > 24°C at the surface and from 6 °C to >20°C at the bottom. The general pattern of currents in the Gulf may be rapidly modified in response to intense local atmospheric forcing (winds) and river plume (Querin et al, 2007;Malačič & Petelin, 2009). The region is highly influenced by the Bora, a north-easterly wind characterized by strong intensity that is able to mix the entire water column also due to the shallow depth of the basin (Querin et al, 2007).…”
Section: Study Sitementioning
confidence: 99%
“…The general pattern of currents in the Gulf may be rapidly modified in response to intense local atmospheric forcing (winds) and river plume (Querin et al, 2007;Malačič & Petelin, 2009). The region is highly influenced by the Bora, a north-easterly wind characterized by strong intensity that is able to mix the entire water column also due to the shallow depth of the basin (Querin et al, 2007). The dominant sediment type in the Gulf is sandy-mud but the composition of soft bottoms can vary from sands with patches of rocks to detrital mud (Brambati & Catani, 1988).…”
Section: Study Sitementioning
confidence: 99%
“…As in Querin et al (2006), the rivers are included by introducing small channels in the bathymetry that simulate the river bed close to the coast. Velocity is imposed at the upstream end of each channel, with the prescribed discharge rate being obtained by multiplying the velocity by the cross sectional area of the channel.…”
Section: Mitgcmmentioning
confidence: 99%